Green tourism in education and research to build Bali State Polytechnic’s brand image and loyalty - Astawa, I Ketut; Armoni, Ni Luh Eka; Suardani, Anak Agung Putri; Ruki, Made (Technium Social Sciences Journal, 2022)
The purpose of the study was to analyze the application of green tourism integration in education and research to build Bali State Polytechnic’s (BSP) brand image and its impacts on stakeholders’ loyalty. The concern of academics and practitioners for the environment and the inclusion of green tourism in campus management is important. However, in the context of integrating green tourism in education and research to build a brand image of educational institutions and stakeholder loyalty, further investigation is needed. The number of research respondents is 60 representatives of study programs, alumni, and users. Determination of respondents is done by purposive sampling. Data collection techniques by observation, interviews, questionnaires, and documentation. Interviews were conducted in a semi-structured manner using an interview guide. The statistical method used is Partial Least Square with SmartPLS 3.3.9 program. The results showed that the application of green tourism integration in education and research positively and significantly affected the brand image of BSP. In addition, the brand image of BSP affects the Willingness to Pay More. This study is based on a way to encourage stakeholders to engage with tuition fees per semester. BSP’s brand image also influences Willing to Support BSP. This means that the higher the brand image formed, the higher the Willingness to Support studying at BSP. Furthermore, BSP’s brand image has a positive and significant effect on the Willingness to Recommend BSP.